GREEBO: Sustainability Eco-Friendly Marketing as Shortcuts for SMEs to Compete in The 5.0 Society Era - Diana Aqmala; Febrianur Ibnu Fitroh Sukono Putra (AIBPM Publisher, 2022)
Purpose: Improve business performance by implementing a eco-friendly marketing sustainability model to penetrate the international market in the 5.0 society era. Methodology: The research method is an exploratory qualitative approach by collecting data based on in-depth interviews with related informants. The sampling technique is purposive sampling, in which the main criteria are SMEs assisted by the Central Java Government. The research analysis flow is data collection, data reduction, data presentation, and concluding. Findings: The results show the